Malignant melanoma of parotid glands from a neglected lesion: A case report - Mahsa Ahadi (Wiley, 2021)
Abstract Observing a metastatic malignant melanoma and its primary lesion at the same time is rare. The histopathological detection of any unusual pigmented lesion is critical.